Analysis Of Village Financial Management Principles at Village Office X - Aprillia Putri Ning Tyas; Ferby Mutia Edwy (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of village financial management principles in Village X based on Home Affairs Ministerial Regulation No. 20 of 2018, with a focus on the principles of transparent, accountable, participatory, and orderly and disciplined budgeting. The study used qualitative methods through interviews and documentation. The results showed that the implementation of village financial management principles is not optimal. In terms of accountable, the village still experiences data input errors in the Village Financial Management System (Siskeudes) and obstacles in the timeliness of reporting, which affects the quality of accountable. In terms of transparent, although budget information is published through billboards, billboard updates are not carried out routinely so that the community does not always receive the latest information. In terms of participatory principles, community involvement in village deliberations is still dominated by village officials and certain figures, while the participatory of general community groups is at an optimal level. In the application of the principles of orderly and disciplined budgeting, budget implementation has not been optimal due to delays in administration, minimal understanding of technical regulations among village officials, and sudden policy changes without adequate training support, so that they are not fully consistent with established plans and schedules. This study recommends improving the competence of village officials, developing flexible internal SOPs, and optimizing the village financial information system as improvement steps to achieve more effective financial governance.